Instrumentação e montagem da mesa cirúrgica para sinusectomia via endoscópica - Queiroz de Aguiar, Lucas; Bezerra Freitas, Rayane; Maciel, Ana Luisa Silva; de Azevedo Queiroz, Raissa; Dantas Palmeira, Wendell (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Introduction: The objective of endoscopic sinus surgery is to return adequate functionality of the paranasal sinuses, with recovery and restoration of the sinus mucosa, in which the use of the endoscope makes the surgery less invasive and more effective. Objectives: This review article proposes to list the surgical instruments used in endoscopic sinus surgery, as well as how the surgical table is prepared. Methods: Didactically, real images of surgical instruments and the surgical table intended for instrumentation. Conclusion: The use of surgical instruments correctly allows the surgical procedure to be more effective and achieve its objective.